Hygienic evaluation of the Resourcify GmbH concept for recovering raw materials from recyclable medical devices after surgery - Kramer, Axel; Brill, Florian H. H. (German Medical Science GMS Publishing House, 2024)
In addition to emissions harmful to the environment, a significant amount of waste is generated in hospitals. In recognition of the fact that medical devices (MDs) contain valuable raw materials, such as rare earth elements, other metals, and high-quality plastics, a recycling concept has been developed. The project was examined for safety and feasibility from a hygiene point of view with sustainability in mind in order to create a reference solution for other areas as applicable. The recycling process begins when the MDs accumulate in the surgical facility and are separated into recyclable and disposable parts. The recyclable parts are subjected to wipe disinfection and collected in closed boxes until they are taken away, while the non-recyclable parts are sent for disposal. The recyclable waste, including the transport boxes, is steam-disinfected in a fractionated vacuum process before recycling. The waste is then recycled, and the emptied transport boxes are made available for re-collection by the surgical facility.The analysis of the overall recycling process shows that infectious risks both for the employees who collect, transport, and recycle the MDs and for the environment are neglectable.